1977
DOI: 10.1017/s0022112077002183
|View full text |Cite
|
Sign up to set email alerts
|

Magnus effect in saltation

Abstract: High-speed motion pictures (2000 frames/s) of saltating spherical glass microbeads (of diameter 350–710 μm and density 2·5 g/cm3) were taken in an environmental wind tunnel to simulate the planetary boundary layer. Analysis of the experimental particle trajectories show the presence of a substantial lifting force in the intermediate stages of the trajectories. Numerical integration of the equations of motion including a Magnus lifting force produced good agreement with experiment. Typical spin rates were of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
228
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(255 citation statements)
references
References 12 publications
20
228
7
Order By: Relevance
“…This additional force can enhance significantly the height and length of the saltating trajectory [7]. However, the general features found above remains qualitatively correct (see for example [8]).…”
Section: Saltation Motionmentioning
confidence: 77%
“…This additional force can enhance significantly the height and length of the saltating trajectory [7]. However, the general features found above remains qualitatively correct (see for example [8]).…”
Section: Saltation Motionmentioning
confidence: 77%
“…The wind tunnel experiment of White and Schulz (1977) shows the distributions of launch velocity and angle have a peak. Nalpanis et al (1993) found that the probability distributions of resultant lift-off velocity and angle are similar to a log-normal distribution.…”
Section: The Distribution Of Resultant Lift-off Velocity and Angle Ofmentioning
confidence: 99%
“…White and Schulz, 1977;Willetts and Rice, 1986;Anderson and Hallet, 1986;Werner and Haff, 1988;Anderson and Haff, 1988;Sørensen, 1991;Haff and Anderson, 1993;Nalpanis et al, 1993;Rice et al, 1995Rice et al, , 1996Dong et al, 2002a;Namikas, 2003). If the probability distributions of the horizontal and vertical lift-off velocities or the resultant lift-off velocity and angle of saltating grains are known, the proportion of the number of grains with a given resultant lift-off velocity and lift-off angle will be acquired, then the macroscopic statistic of particles can be deduced from the representative trajectories of saltating grains.…”
Section: Introductionmentioning
confidence: 99%
“…There are complex mass and energy exchanges among saltating grains, grains on the surface, and the airflow. Moreover, there are processes difficult to consider in theoretical models such as the Magnus effect and Saffman lifting force (White and Schulz, 1977;Zou et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is also difficult from photographic images to interpret the velocity of sand particles at very low heights such as below 0.5 cm where the grains are too crowded, and at higher height, such as over 7 cm, where the moving grains are too few (Zou et al, 2001). Because a blowing sand cloud is group movement composed of a large number of randomly interacting sand particles with various velocities (e.g., White and Schulz, 1977), the statistical average of particle velocities should be obtained using a sufficient number of sand particles.…”
Section: Introductionmentioning
confidence: 99%